2 5' Untranslated Region-Based Detection of Genetically Diverse APPV Strains in US Midwest. (12th April 2022) - Eaton, Christian; Sutton, Kylee; Mote, Benny E; Burkey, Thomas E; Borza, Tudor; Loy, J Dustin; Ciobanu, Daniel C
Abstract: Atypical porcine pestivirus (APPV), an RNA virus member of the Flaviviridae family, has been associated with congenital tremor in newborn piglets. Previous qPCR-based assays, targeting the polyprotein coding sequences of APPV, were unable to detect the virus in novel cases of congenital tremor originated from multiple swine farms from the U.S. Midwest (MW). The polyprotein coding genes of APPV were characterized by a low level of sequence conservation ranging from 58.2 to 70.7% among 15 global APPV strains. In contrast, the 5' untranslated region (UTR) was found to have a much greater degree of sequence conservation of 81.0% seen among the 15 global and new 4 MW strains, and as high as 91.5% when comparing only 5 MW strains. The complete 5' UTR sequence of the APPV strains originated from MW was obtained by utilizing the template switching approach followed by amplification and dideoxy sequencing. Notably, previously identified potentially crucial regions for the correct function of the APPV internal ribosome entry site (IRES) were found to overlap with the most highly conserved 5'UTR segments, suggesting their functional role in viral protein translation. By targeting 100% conserved 5'UTR regions across 19 global and MW strains, a new qPCR assay was designed which was able to detect APPV in well documented cases of congenital tremor which originated from 5 MW farm sites (1-18 samples/site). The assay was found to have a detection sensitivity of 6.5 APPV copies (Cq 38.4). Due to the potential functional importance of the highly conserved 5'UTR sequences targeted by our newly developed qPCR assay, we expect that assays targeting this region would broadly detect APPV strains that are diverse in space and time.